Aerobic oxidation of starch catalyzed by isopolyoxovanadate Na4Co(H2O)6V10O28. (6th March 2015) - Chen, Xiaoli; Yan, Siqi; Wang, Hang; Hu, Zhiyun; Wang, Xiaohong; Huo, Mingxin
Highlights: Prepared catalyst Na4 Co(H2 O)6 V10 O28 and applied in partial oxidation of starch. Oxidation of starch with oxygen was realized under mild reaction conditions. Give a high oxidation degree and 86 wt.% yield of solid oxidized starch. Control the oxidation reaction occurred only outside of the starch granule. Abstract: The partial oxidation of starch was achieved in the presence of oxygen with Na4 Co(H2 O)6 V10 O28 ·18H2 O (abbreviated as CoV10 ) as catalyst. The oxidation degree of starch was determined by FT-IR, XRD and SEM measurements, which indicated that the aerobic oxidation of starch was promoted by oxidative catalyst CoV10 . The application of CoV10 could give a high oxidation degree (DO) of 1.35 COOH/100 GU and 2.07 CO/100 GU with 86 wt.% yield of solid starch under mild reaction conditions (pH = 6; reaction time, 8 h; temperature, 50 °C; catalyst amount, 8 mg, when 1.5 g starch was used as substrate; atmospheric pressure). Among some vanadium compounds, CoV10 exhibited 4-fold activity higher than orthovanadate due to its coordination effect of cobalt and V10 O28 . Meanwhile, CoV10 could be recycled for six times with only a slight decrease in activity. Thus, CoV10 /O2 is one of the most efficient systems for partial oxidation of starch reported so far.